(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article refers to the equivalents of sentences as means of expressive syntax. Attention is drawn to the various modal types of word-sentences, incomplete sentences and address sentences. It is determined that equivalents of sentences in the context of a literary text often operate in the style of verbal-сolloquial speech dialogs. It is investigated expressive functions of the affirmative, negative, interrogative, incentive, emotionally-evaluative, and word-sentences of the speech etiquette. It is substantiated the view that the amplification word-sentences creates emphatically intone, sensory intense complex of statement that allows author to organically include the subjective world of characters into his narrative. It is revealed that unfinished sentences are the means of recreation certain emotional states of the characters (confusion, despair, hesitation, grief, indecision, delight, joy, determination, etc.). Vocative sentences or address sentences are highlighted among the expressive means, emotional tone of which is provided by special intonation. It is revealed that that the main meaning of these not divisioned communiques is incentive, addressed to the person to whom appeal. Units with distinct incentive action are highlighted among the address sentences, which realize modal meaning in literal speech (the order, request, reservations, etc.) through context. It is proved that address sentences combine appeal and expressive features, can express not only address to the recipient, but also the attitude of the speaker to it. It is concluded that syntactical expressive means distinguished by art-descriptive figurative capacity, the ability to display a wide range of modal values, reproduce the emotional state of the characters of artistic composition.